An Annotated Translation of Love is A Frenzy by Charlotte Lamb - Putri, Erna Pranata; Bangun, Setia (Journal of Language and Literature, 2014)
This is an annotated translation research, a translation with commentary. The problems of this research are: 1) What are the difficulties encountered in the course of translation? 2) How does the researcher cope with the difficulties in order to get the solutions? This research aims to: 1) find out the difficulties coming up when translating the source text; 2) solve the difficulties that come across when translating the source text. The methods used in this research are introspective and retrospective methods. Relevant translation strategies and theories are used in solving the problems that are encountered during the translation. The results of this research show that there are 75 items of difficulties Out of 75 items of difficulties, there are 25 items annotated in this research, namely 15 words, 8 phrases, 1 clause and 1 sentence. Relevant translation principles, strategies and theories are used in solving the difficulties that are encountered during the translation. Furthermore, of the 25 items of annotated data, there are 12 strategies employed, namely 1 synonym, 7 naturalization, 1 clause structure change, 1 distribution change (reduction), 2 calque, 2 cohesion change (pronominalization), 4 explicitness change, 2 antonymy, 1 transposition, 1 trope change, 2 paraphrase, 1 unit shift. In order to solve the difficulties, the researcher employed translation principles, strategies and theories. This implies that in order to solve the difficulties encountered in a translation, the translator should understand or have knowledge on principles, strategies and theories of translation. Keywords: annotated translations, problems, solutions